Detection of lard via fluorescent fiber probe sensor utilizing graphene quantum dots - Che Lah, Che Nur Hamizah (2018)
Graphene quantum dots (GQDs) recently emerge as a superior and universal fluorophores because of their unique combination of a number of key merits, including small in size, excellent photostability, biocompatibility, and highly tunable photoluminescence properties. These glowing carbon nanocrystals provide unprecedented opportunities for bioimaging and optical sensing. In this research, the usage of optical fiber which is tapered multimode fiber (TMMF) is used for detection of lard. Prior to this, several methods that have been introduced include electronic nose (zNose), Fourier-transform infrared spectroscopy, high performance liquid chromatography/tandem mass spectroscopy (HPC-MS/MS) and polymerase chain reaction (PCR). However, all of these techniques require large detector and are time consuming. In this research, detection of lard was done using optical fiber characterization of GQDs and GQDs coated with gold nanoparticles (Au-GQDs), more reliable and environmentally friendly fluorescence fiber probe sensor. TMMF with 20nm diameter was chosen and then coated with GQDs or Au-GQDs using drop casting method. The main interest of the investigation was to identify the effect of combining TMMF with GQDs and Au-GQDs as the nanoparticles. The characterization of annealing effects at different temperature of the GQDs and Au- GQDs shows that at 70oC and 100oC respectively gives the highest sensitivity. Three types of TMMF probe sensors were then used to detect lard with different concentrations, ranging from 20% to 100%. The fluorescence responses of the sensor were investigated for uncoated TMMF and TMMF coated with GQD and Au-GQDs. The result from this study shows that TMMF coated with GQDs and annealed in 70oC gives better and strong fluorescence emission peak at 652nm. However, the sensitivity of lard detection achieved is 0.034/a.u.%. By introducing Au NPs to GQD creating Au-GQDs TMMF probe sensor, the peak shifted to 680nm and give the highest sensitivity and linearity of detection which are 0.042/a.u.% and 85% respectively at 100oC. The difference in the annealing temperature resulted in different carbon-carbon bond formation between the carbons of fats bound with the carbon from GQDs. Then, the mixture of carbon-carbon bond became excited and the energy was emitted as fluorescence. Throughout this research work, an in-depth understanding on GQDs and Au-GQDs as fluorescent sensing platform in detection of lard concentration via fluorescence fiber probe sensor was studied. As well as an investigation on the binding process between GQDs and Au-GQDs with the lard to perform fluorescence emission. Ultimately, this research work achieved its goals to develop a method to detect lard concentration via fluorescence fiber probe sensor.